Efektivitas Pembelajaran Jarak Jauh (PJJ) pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SDN 1 Darmacaang - Selamet; Nisa Usolihah (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Since the emergence of the Covid-19 outbreak in Indonesia in March, The Indonesian government and the Ministry of Education and Culture have implemented online learning or distance learning to reduce the spread of the virus. The Regent and the Head of the Ciamis Regency Education Office gave orders for all students to study at home and imposed an extension of Distance Learning time both online and offline during the Covid-19 emergency period from January 26, 2021 to 8 February 2021.The purpose of this study was to describe the effectiveness of Distance Learning for students at SDN 1 Darmacaang. This research uses qualitative research with a descriptive qualitative approach (case study). Data collection techniques using observation, documentation and tests. Distance learning in the subject of Islamic religious education and character is less effective to do. This can be seen from the test results given to students from each material being taught.